Current Management of Cardiac Implantable Electronic Device Infections by Infectious Disease Specialists. (28th June 2016) - Liang, Stephen Y.; Beekmann, Susan E.; Polgreen, Philip M.; Warren, David K.
Abstract: Management guidelines for cardiac implantable electronic device infections exist, but practice patterns of infectious disease (ID) specialists are not well known. We found that while many ID specialist practices mirror existing guidelines, a combination of complete device removal and prolonged antimicrobial therapy is favored when Staphylococcus aureus is involved.